2016
DOI: 10.1017/pab.2016.26
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the completeness of the fossil record: comparison of different methods applied to parareptilian tetrapods (Vertebrata: Sauropsida)

Abstract: As paleontological studies are generally distorted by gaps and biases in the fossil record, it is important to assess its completeness. Here we address the fossil record of Parareptilia, a Permian–Triassic amniote clade, applying two measures of specimen completeness: the skeletal completeness metric (SCM) and the character completeness metric (CCM). The SCM quantifies how much of the skeletal material of a taxon is preserved, whereas the CCM measures the amount of phylogenetic information available. The latte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(55 citation statements)
references
References 68 publications
(89 reference statements)
1
54
0
Order By: Relevance
“…); synapsid‐grade pelycosaurs (Brocklehurst & Fröbisch ); parareptiles (Verrière et al . ); and bats (Brown et al ). Silhouettes used include work by S. Hartman, and D. Bogdanov (see http://phylopic.org for full licensing information).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…); synapsid‐grade pelycosaurs (Brocklehurst & Fröbisch ); parareptiles (Verrière et al . ); and bats (Brown et al ). Silhouettes used include work by S. Hartman, and D. Bogdanov (see http://phylopic.org for full licensing information).…”
Section: Resultsmentioning
confidence: 99%
“…Verrière et al . () examined only genus‐level taxa of parareptiles, and this may potentially explain the higher completeness of parareptiles in relation to all other terrestrial groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tutin & Butler [48] found a significant relationship between skeletal completeness and character completeness metrics for plesiosaurs, and between plesiosaur and ichthyosaur completeness, suggesting common controls on skeletal preservation in both groups; this could feasibly include a lagerstätten bias. Lagerstätte biases in completeness may not be present for all groups; however, Verriere et al [49] found no evidence for lagerstätte effects on parareptile diversity and in turn no correlation between their diversity and skeletal or character completeness metrics.…”
Section: Ichthyosauriamentioning
confidence: 94%